Biological control as an integrated control method in the management of aquatic weeds in an urban environmental and socio-political landscape : case study : Cape Town Metropolitan Area - Stafford, Martha Louise (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2014)
Aquatic weeds transform and degrade the ecosystems which they invade, impacting various aspects of their surroundings ranging from the community level to disrupting important processes affecting ecosystem services. All of the major aquatic weeds of South Africa are found in the Cape Town Metropolitan Area. Landowners, whether private or public, are legally obliged to manage the listed invasive species through applying environmentally acceptable methodologies. This thesis provides an overview of the strategic management options, prevention, early detection, rapid response and eradication of new invasions, and containment and control species of established species. It discusses the different control methods available for managing aquatic weeds, namely mechanical, manual, chemical and biological, and the integration of different methods to improve their effectiveness. Although various studies have shown that biological control is the most cost"“effective, environmentally-friendly and sustainable method, it is not yet fully integrated into weed management programmes in South Africa. In addition, the successes achieved in other parts of the world with the control of water hyacinth through biological control have not been repeated in the urban environment, despite the fact that South Africa has the highest number of biological control agents available for the weed. Urbanisation puts pressure on the natural environment and ecosystem functioning. Nutrient-enriched waters support aquatic weed growth and pose a challenge to the management thereof, in particular with regard to integrating biological control into management programmes. The aims of this study were to determine the reasons for the lack of integration of biological control into weed management programmes in South Africa, to determine the feasibility of integrating biological control in aquatic weed management programmes in a complex urban environmental and socio-political landscape by means of three case studies in the Cape Town Metropolitan Area, which showed that biological control is feasible in urban environments and should be considered. Two surveys were conducted to determine the reasons for the lack of integration of biological control into weed management programmes. The surveys showed that there is a gap between research and implementation as a result of poor communication, non-supporting institutional arrangements and a lack of appropriate capacity and skills at the implementation level. Recommendations were offered to address these issues.
Keywords: Aquatic weeds -- South Africa -- Cape Town; Aquatic weeds -- Biological control -- South Africa -- Cape Town; Water hyacinth -- Biological control -- South Africa -- Cape Town; Metropolitan areas -- South Africa -- Cape Town